The Joyful Experience in Learning Mathematics - Ricky S. Yabo (Southeast Asian Mathematics Education Journal, 2020)
Southeast Asia Mathematics Education Journal, Volume 10, No 1 (2020)55The Joyful Experience in Learning MathematicsRicky S. YaboDepartment of Education Regional Office VII, Cebu City, Philippinesricky.yabo@deped.gov.phAbstractThis study was conducted to determine the effectiveness of joyfulscaffolds in teachinggrade VIII mathematicsin the Department of Education of the Philippines. Two intact groups were used as the subjects of the study.The experimental and control group were exposed to joyful and traditional scaffolds in teaching respectively. This study includes the pre-post assessments, significant improvements, and significant mean gain differences of students exposed to traditional and joyful scaffolds in teaching mathematics in terms of performance level.The findings of the study revealed that the joyful scaffold in teaching is more effective in improving the students’ mathematics performance compared to the traditional scaffold in teaching and the skills acquired is sufficient enough to prove that these experimental group of students was able to gain experience from joyful approach and a positive change of attitude towards their view on mathematics was realized after the exposure. The cognitive progression was deepened, and attainment of knowledge was enhanced, psychomotor skills were activated and augmented through enjoyable mathematics learning activities, and students’ interests and learning manners were maximized. Furthermore, the joyful scaffold in teaching in this study was immensely efficient in improving the students’ mathematics performance compared to the traditional scaffold in teaching. Moreover, the outcome of this research supports the assertion that employing, relating, or incorporating several joyful media to learning boosted up students’ academic performance especially those who are detached during the classroom discussion.